Development of Desirable Competency Indicators for Nursing Graduates of Rajabhat University - Buosonte, Parin; Lincharoen, Aumporn (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2026)
This research aimed to: 1) develop the components and indicators of desirable competencies for nursing graduates of Rajabhat Universities, and 2) examine the construct validity of the components and indicators of desirable competencies for nursing graduates of Rajabhat Universities. The sample consisted of 252 nursing graduates from Rajabhat Universities, obtained through multi-stage random sampling. The data collection instrument was a rating scale questionnaire with 5 levels of assessment, comprising a total of 43 items. Data analysis was conducted using means, standard deviations, correlation coefficients, and confirmatory factor analysis. The research findings revealed that: 1) The components and indicators of desirable competencies for nursing graduates of Rajabhat Universities consisted of 8 competency domains with 43 indicators, namely: 1) Ethics, professional conduct, and law 11 indicators; 2) Nursing and midwifery practice 7 indicators; 3) Professional attributes 4 indicators; 4) Leadership, management, and quality development 4 indicators; 5) Academic knowledge and research 6 indicators; 6) Communication and interpersonal relationships 3 indicators; 7) Technology and information 4 indicators; and 8) Society 4 indicators. The suitability assessment by 11 experts indicated that all competencies were rated at the highest level of appropriateness. 2) The results of the second-order confirmatory factor analysis of the desirable competency indicator model for nursing graduates of Rajabhat Universities showed that the model demonstrated construct validity and goodness of fit with the empirical data (X2 (576, N = 252) = 632.283, X2/df = 1.098, p – value = 0.0519, CFI = 0.995, TLI = 0.993, RMSEA = 0.020, SRMR = 0.049).